FUNDAMENTALS OF COMMUNICATION FORMATION IN THE TRAINING OF A MODERN FOOTBALL REFEREE (Physical Culture and Sport: Scientific Perspective, 2024)
The article examines the basics of the formation of communication in the training of a modern football referee, it is proved that the expansion of the referee's functions in modern sports, the complication of refereeing tasks, and the diversification of the content of sports activities lead to an increase in the requirements for the personality of a sports referee. The theoretical analysis of the literature on the topic of the study made it possible to highlight several aspects of the professional activity of sports referees: the individual aspect of refereeing is the systematic formation of knowledge, skills and abilities, as well as the abilities of a sports referee with the help of theoretical and practical training in refereeing, in particular in the chosen sport. The components of an effective organized process of training football referees are substantiated, namely: the basics of refereeing theory and methodology (philosophy, mechanics, rules); psychological and pedagogical characteristics of a football referee's personality, his motivation; physical fitness of people for judging; factors ensuring the success of such activities; a system of control and self-monitoring of arbitrators' training. In addition, it is important to determine the means, methods and methodological techniques that ensure the physical, technical and psychological preparation of the judge, the efficiency of his thinking, and, what is important, the ability to communicate, knowledge of native and foreign languages.Within the framework of "Communication Skills" - the art of transmitting and receiving information, we have highlighted four main vectors: situation management (decisions regarding situations) that take place, as it were, "inside" the match directly on the football field; management of situations (decisions regarding situations) around the match (including around the boundaries of the football field); management of partners (assistants, fourth referee), decision regarding information of partners; management of the audience (in particular, the reaction, influence and pressure of the stands, depending on the decisions made by the judge).
Keywords: referee; communication; professional training; football; «Communication Skills»